2020
DOI: 10.3390/molecules25235550
|View full text |Cite
|
Sign up to set email alerts
|

Technologies Employed in the Treatment of Water Contaminated with Glyphosate: A Review

Abstract: Glyphosate [N-(phosphonomethyl)-glycine] is a herbicide with several commercial formulations that are used generally in agriculture for the control of various weeds. It is the most used pesticide in the world and comprises multiple constituents (coadjutants, salts, and others) that help to effectively reach the action’s mechanism in plants. Due to its extensive and inadequate use, this herbicide has been frequently detected in water, principally in surface and groundwater nearest to agricultural areas. Its pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 97 publications
(134 reference statements)
0
49
0
Order By: Relevance
“…Physicochemical processes such as adsorption, membrane filtration, and coagulation have proven to be efficient and economical for removing glyphosate [107,108]. Adsorption is a widely used process for treating and purifying water contaminated with glyphosate due to its simplicity, non-toxicity, low-cost design, and high efficiency.…”
Section: Physicochemical Treatments For Glyphosate Remediationmentioning
confidence: 99%
See 3 more Smart Citations
“…Physicochemical processes such as adsorption, membrane filtration, and coagulation have proven to be efficient and economical for removing glyphosate [107,108]. Adsorption is a widely used process for treating and purifying water contaminated with glyphosate due to its simplicity, non-toxicity, low-cost design, and high efficiency.…”
Section: Physicochemical Treatments For Glyphosate Remediationmentioning
confidence: 99%
“…The adequate selection of adsorbent material is crucial, among the materials that have been used as adsorbents to remove glyphosate from wastewater are clay substances [109], activated carbon [110,111], zeolite [112]; biochar [113,114], graphene oxide and iron-based adsorbing materials [115], resins [116,117]. The glyphosate adsorption process occurs through physical and chemical interactions between the functional groups of the glyphosate molecule (-COOH, -NH 2 , and -PO(OH) 2 ) and the surface of the adsorbent [107]. In general, it has been found that under acidic conditions, the adsorption of glyphosate by different adsorbents is more favorable, so it has been proposed that pH is one of the most determining factors affecting the glyphosate adsorption process [108,113].…”
Section: Physicochemical Treatments For Glyphosate Remediationmentioning
confidence: 99%
See 2 more Smart Citations
“…Glyphosate as a post-emergent, non-selective systemic herbicide eliminating several weed species at the early growth stage is mainly used in agricultural land. Nevertheless, despite agricultural use accounting for 90% of the total usage, glyphosate is also utilised in non-agricultural land such as ruderal, industrial, or urban areas [10,[13][14][15][16]. Its action is based on the inhibition of the 5-enolpyruvyl-shikimate-3-phosphate synthase, an essential enzyme responsible for the synthesis of amino acids in the shikimate pathway in plants and in some microorganisms.…”
Section: Introductionmentioning
confidence: 99%